Small Bowel Intussusceptions by Ultrasound (Journal of Medical Sciences, 2018)
The purpose of this study was to evaluate the typical ultra-sonographic findings of transient Small Bowel Intussusceptions (SBI)) in paediatrics. 6 transient SBI (male: female =4:2, age: 7–120 months (mean 38.months)) patients diagnosed on ultrasonography were retrospectively evaluated. The findings of location, diameter, thickness of outer rim, and inclusion of mesenteric lymph nodes within intussusceptions were compared. In the transient SBI, the head of intussusceptions was located in the right lower quadrant (RLQ) in 3 (50%), the right upper quadrant (RUQ) in 1 (16,1%) and the periumbilical area in 2 (33,4%) cases. The anteroposterior (AP) diameter ranged from 0.9–2.5 cm (mean 1.38 cm), and thickness of outer rim ranged from 0.10–0.34 cm (mean 0.26 cm). No mesenteric lymph nodes were contained within the intussuscipiens. In conclusion, the transient SBI occurs predominantly in the RLQ or periumbilical region has a smaller AP diameter, a thinner outer rim, and dose not contain mesenteric lymph nodes.Intussusception is a common abdominal emergency that requires prompt diagnosis and adequate management.1 The wider use of ultrasonography and its improved resolution and better appreciation, transient small bowel intussusception (SBI) is frequently visualized on practical daily ultrasound. In recent literature,2–5 careful ultrasonographic examination and/or interpretation of CT scans have disclosed many SBIs that were reduced spontaneously without any intervention. Conservative observation was warranted in these patients by Doi et al.5  The purpose of this article is to evaluate the typical ultrasonographic findings of transient small bowel intussusceptions (SBI).